High-performance NiO-based acetone gas-sensitive sensing element and preparation method thereof
By introducing a small layer of Ti3C2Tx and freeze-drying technology with high specific surface area into the NiO gas-sensitive sensor, p-n TiO2/NiO composite gas-sensitive element was prepared, which solved the problem of reduced moisture resistance and selectivity caused by traditional methods, and achieved better gas-sensitive performance and stability.
Patent Information
- Application Number
- CN202411867906.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional methods of preparing NiO gas-sensitive sensors result in their loss of excellent anti-wet properties and selectivity.
A small layer of Ti3C2Tx with high specific surface area and surface activity was introduced into the NiO preparation system, and the agglomeration between the powder particles was reduced by freeze-drying to prepare a p-n TiO2/NiO composite gas-sensitive element.
On the basis of ensuring NiO's moisture resistance and rapid response recovery rate, the gas-sensitive response value, selectivity and cycling stability are improved.
Smart Images

Figure CN119666938A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas sensor material preparation, and relates to a high-performance NiO-based acetone gas-sensitive sensor element. The invention also relates to a method for preparing the high-performance NiO-based acetone gas-sensitive sensor element. Background Art
[0002] Metal oxide semiconductor gas sensors are highly favored due to their excellent sensitivity, fast response / recovery characteristics, low cost, simple electronic interface and convenient use. They play an important role in many fields such as atmospheric monitoring, safety inspection, food preservation, medical testing and national defense and military. As a typical p-type metal oxide semiconductor material, NiO has excellent catalytic activity, moisture resistance, selectivity and fast response recovery rate, making it an important material for preparing gas sensors. However, due to the agglomeration of NiO powder and its unique shell-shell conduction mechanism, it has problems such as low sensitivity in practical applications.
[0003] When the ambient atmosphere changes from air to reducing gas, the oxygen adsorbed on the NiO surface desorbs and injects electrons into NiO, causing the hole concentration on the NiO surface to decrease. This will cause the resistance of the NiO gas sensor to increase sharply, and the degree of change in the resistance of the NiO gas sensor reflects its ability to respond to the target gas. Therefore, adjusting the NiO hole concentration to increase the change value of the NiO surface hole concentration during the atmosphere conversion is an effective strategy to enhance the gas sensing performance of NiO. By increasing the specific surface area of NiO, the adsorption / desorption amount of oxygen on its surface can be increased, thereby increasing the degree of change in the hole concentration on the NiO surface. In addition, combining NiO with n-type semiconductor oxides can form a pn junction depletion layer at their interface, thereby reducing the hole concentration in NiO and increasing the resistance of the NiO gas sensor in a reducing atmosphere. However, the traditional method of constructing NiO composite materials, although it can increase the specific surface area of NiO and construct a pn junction to improve its response value, is easy to change the response type of NiO-based gas sensors, causing the prepared gas sensors to lose their excellent moisture resistance and selectivity. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a high-performance NiO-based acetone gas-sensitive sensor element, and to prepare a pn TiO 2 / NiO composite gas sensor solves the problem that gas sensors prepared by traditional preparation methods lose their excellent moisture resistance and selectivity.
[0005] Another object of the present invention is to provide a high-performance NiO-based acetone gas-sensitive sensor element prepared by the above preparation method.
[0006] The first technical solution adopted by the present invention is a method for preparing a high-performance NiO-based acetone gas-sensitive sensor element, and the specific steps are as follows: Step 1: Mix lithium fluoride and hydrochloric acid, add titanium aluminum carbide and stir evenly, and wash with dilute hydrochloric acid and deionized water to obtain a multilayer Ti 3 C 2 T x solution, and then multilayer Ti 3 C 2 T x The solution was dispersed in deionized water and ultrasonically treated to obtain a few-layer Ti 3 C 2 T x Suspension; Step 2: Nickel nitrate hexahydrate, hexadecyltrimethylammonium bromide and few-layer Ti 3 C 2 T x The suspension was dispersed in a mixed solution of methanol and deionized water, and then subjected to hydrothermal reaction. Finally, NiO / TiO was obtained after washing, freeze drying and heat treatment. 2 powder; Step 3: NiO / TiO 2 The powder was mixed with pine alcohol and coated on Al 2 O 3 The ceramic tube and the surface of the annular Au electrode were calcined at high temperature. After cooling in the furnace, the Ni-Cr heating wire was passed through the ceramic tube. Four Pt wire pins and two heating wire pins were welded to the hexagonal base to obtain a high-performance NiO-based acetone gas sensor, and the gas sensing performance of the gas sensor was evaluated.
[0007] The present invention is also characterized in that: The specific method of step 1 is: Step 1.1, adding lithium fluoride to hydrochloric acid and mixing evenly to obtain a hydrofluoric acid etching solution; Step 1.2, titanium carbide aluminum powder is added to a hydrofluoric acid etching solution in 3 to 5 times, stirred at 45°C to 50°C for 20 to 24 hours to obtain a mixture, and the mixture is washed with 3 mol / L dilute hydrochloric acid and deionized water respectively until the pH of the supernatant reaches 5.9 to 6.1 to obtain a multilayer Ti 3 C 2 T x Solution; Step 1.3: Multilayer Ti 3 C 2 T x The solution was dispersed in deionized water and ultrasonically treated, centrifuged and the dark green supernatant was collected to obtain the few-layer Ti 3 C 2 T x Suspension.
[0008] In step 1.1, the molar ratio of lithium fluoride to hydrochloric acid is 1:4, and the concentration of hydrochloric acid is 5-12M; in step 1.2, the mass ratio of lithium fluoride to titanium aluminum carbide powder is 1.55-1.58:1.
[0009] In step 1.3, multilayer Ti 3 C 2 T x The temperature of the solution for ultrasonic treatment is 25~70℃, the treatment time is 1~6h, and the obtained few-layer Ti 3 C 2 T x The concentration of the suspension is 0.01~0.1 g / mL.
[0010] The specific method of step 2 is: Step 2.1, a certain amount of nickel nitrate hexahydrate, hexadecyltrimethylammonium bromide and few-layer Ti 3 C 2 T x The suspension is sequentially dispersed in a mixed solution of methanol and deionized water to obtain a hydrothermal solution; Step 2.2, the hydrothermal solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene for hydrothermal reaction, the hydrothermal temperature was 100-200 ° C, the hydrothermal time was 12-36 h, after the hydrothermal reaction was completed, the hydrothermal product was washed 2-4 times with anhydrous ethanol, and then washed 2-4 times with deionized water to obtain Ni(OH) 2 / Ti 3 C 2 T x Aqueous solution; Step 2.3: Ni(OH) 2 / Ti 3 C 2 T x The aqueous solution is freeze-dried at a temperature of -20 to -50 °C and a freezing time of 12 to 36 hours to obtain fluffy Ni(OH) 2 / Ti 3 C 2 T x Precursor; Step 2.4: Ni(OH) 2 / Ti 3 C 2 T x The precursor is placed in a tube furnace for a one-step heat treatment to obtain NiO / TiO 2 powder.
[0011] In step 2.1, the mass ratio of nickel nitrate hexahydrate to hexadecyltrimethylammonium bromide is 0.5-0.55:1, and the few-layer Ti3 C 2 T x The mass percentage of nickel nitrate hexahydrate is 1-15wt%; The mass ratio of nickel nitrate hexahydrate, methanol and deionized water is 1:100:20.
[0012] In step 2.4, the atmosphere in the tube furnace is oxygen, the flow rate is 400 mL / min, the heat treatment temperature is 300~500℃, and the holding time is 1~3 h.
[0013] The specific method of step 3 is: Step 3.1: NiO / TiO 2 The powder and pinene alcohol are mixed into a slurry with a certain viscosity, NiO / TiO 2 The powder mass and pineol volume ratio is 0.03~0.06:12~17 mg / μL, and then the slurry is evenly coated on the Al 2 O 3 Ceramic tube surface and ring-shaped Au electrode; Step 3.2: Then coat the NiO / TiO 2 Powdered Al 2 O 3 The ceramic tube was placed in a muffle furnace and calcined at 350-380 ℃ for 2-2.5 h to fully volatilize the pine alcohol. After cooling in the furnace, the Ni-Cr heating wire was passed through the ceramic tube, and four Pt wire pins and two heating wire pins were welded on the hexagonal base to obtain a high-performance NiO-based acetone gas sensor. Step 3.3: Place a high-performance NiO-based acetone gas sensor into a gas reaction chamber for gas sensing. Use a DC regulated power supply as a heating source to control the working temperature of the gas sensor by adjusting the output power. Use an electrochemical workstation to measure and record the resistance value. Inject a detection gas of a certain concentration and humidity into the reaction chamber to detect the resistance change and evaluate the NiO / TiO 2 Gas sensing performance.
[0014] The gas to be detected introduced in step 3.3 is acetone, methanol, xylene or isopropanol, the gas concentration is 3-300 ppm, the reaction temperature is 240-400 °C, and the reaction humidity is 10-85%.
[0015] The second technical solution adopted by the present invention is to prepare a high-performance NiO-based acetone gas-sensitive sensor element using a high-performance NiO-based acetone gas-sensitive sensor element preparation method. The beneficial effects of the present invention are: (1) The present invention combines a few-layer Ti with high specific surface area and surface activity 3 C 2 T xThe NiO-based composite gas sensor is introduced into the NiO preparation system, and the freeze-drying method is used to reduce the agglomeration between the powder particles. The NiO-based composite gas sensor prepared by this method has a more excellent gas-sensitive response value, selectivity and cycle stability on the basis of ensuring the moisture resistance and fast response recovery rate of NiO. (2) The preparation method of the present invention first uses Ti 3 C 2 T x Heat treatment in oxygen transforms it into TiO 2 , and maintain its ultra-thin morphology, by adding a small amount of Ti 3 C 2 T x As the growth substrate of NiO, the NiO nanosheets have a higher specific surface area and form a pn junction to reduce the surface hole concentration of NiO, ensuring the P-type response of the NiO-based composite gas sensor while improving its response value; secondly, this method adopts the method of first preparing Ni(OH) 2 / Ti 3 C 2 T x Precursor, and then heat treatment to Ni(OH) 2 and Ti 3 C 2 T x Simultaneous oxidation to obtain pn TiO 2 / NiO, making NiO and TiO 2 It has higher binding properties, which helps the transfer of carriers and the formation of a depletion layer, thereby improving the response value of the composite gas sensor; finally, this method uses a freeze-drying method to reduce the agglomeration between the composite powders, provides a transmission channel for the gas to be detected, helps to improve its response value, and shortens the response recovery time. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The few-layer Ti prepared in Example 1 of the present invention 3 C 2 T x SEM photos of Figure 2 The TiO prepared in Example 1 of the present invention 2 / SEM photo of NiO powder; Figure 3 The TiO prepared in Example 1 of the present invention 2 Acetone concentration response test diagram of / NiO composite powder gas sensor; Figure 4 The TiO prepared in Example 2 of the present invention 2 Selective response test diagram of / NiO composite powder gas sensor; Figure 5 The TiO prepared in Example 2 of the present invention 2 Humidity response value test chart of / NiO composite powder gas sensor; Figure 6 The TiO prepared in Example 2 of the present invention 2 Cyclic stability curve of / NiO composite powder gas sensor. DETAILED DESCRIPTION
[0017] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0018] The preparation method of high-performance NiO-based acetone gas-sensitive sensor element comprises the following specific steps: Step 1: Mix lithium fluoride and hydrochloric acid, add titanium aluminum carbide and stir evenly, and wash with dilute hydrochloric acid and deionized water to obtain a multilayer Ti 3 C 2 T x solution, and then multilayer Ti 3 C 2 T x The solution was dispersed in deionized water and ultrasonically treated to obtain a few-layer Ti 3 C 2 T x Suspension, the specific method is: Step 1.1, adding lithium fluoride to hydrochloric acid and mixing them evenly to obtain a hydrofluoric acid etching solution; wherein the molar fraction ratio of lithium fluoride to hydrochloric acid is 1:4, and the concentration of hydrochloric acid is 5-12M.
[0019] Step 1.2, adding titanium aluminum carbide powder to a hydrofluoric acid etching solution in 3 to 5 times, stirring at 45°C to 50°C for 20 to 24 hours to obtain a mixture, wherein the mass ratio of lithium fluoride to titanium aluminum carbide powder is 1.55 to 1.58:1, and the mixture is repeatedly washed with 3 mol / L dilute hydrochloric acid and deionized water, respectively, until the pH of the supernatant reaches 5.9 to 6.1, to obtain a multilayer Ti 3 C 2 T x Solution; Step 1.3: Multilayer Ti 3 C 2 T x The solution was dispersed in deionized water and ultrasonically treated at a temperature of 25-70 °C for 1-6 h. The dark green supernatant was collected by centrifugation to obtain a few-layer Ti 3 C 2 T x Suspension, few layers of Ti 3 C 2 T x The concentration of the suspension is 0.01~0.1 g / mL.
[0020] Step 2: Nickel nitrate hexahydrate, hexadecyltrimethylammonium bromide and few-layer Ti 3 C 2 T x The suspension was dispersed in a mixed solution of methanol and deionized water, and then subjected to hydrothermal reaction. Finally, NiO / TiO was obtained after washing, freeze drying and heat treatment. 2 Powder, the specific method is: Step 2.1, a certain amount of nickel nitrate hexahydrate, hexadecyltrimethylammonium bromide and few-layer Ti 3 C 2 T x The suspension is sequentially dispersed in a mixed solution of methanol and deionized water to obtain a hydrothermal solution, wherein the mass ratio of nickel nitrate hexahydrate to hexadecyltrimethylammonium bromide is 0.5-0.55:1, and the few-layer Ti 3 C 2 T x The mass percentage of nickel nitrate hexahydrate is 1-15wt%; the mass ratio of nickel nitrate hexahydrate, methanol and deionized water is 1:100:20.
[0021] Step 2.2, the hydrothermal solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene for hydrothermal reaction, the hydrothermal temperature was 100-200 ° C, the hydrothermal time was 12-36 h, after the hydrothermal reaction was completed, the hydrothermal product was washed 2-4 times with anhydrous ethanol, and then washed 2-4 times with deionized water to obtain Ni(OH) 2 / Ti 3 C 2 T x Aqueous solution; Step 2.3: Ni(OH) 2 / Ti 3 C 2 T x The aqueous solution is freeze-dried at a temperature of -20 to -50 °C and a freezing time of 12 to 36 hours to obtain fluffy Ni(OH) 2 / Ti 3 C 2 T x Precursor; Step 2.4: Ni(OH) 2 / Ti 3 C 2 T x The precursor was placed in a tube furnace for a one-step heat treatment. The atmosphere in the tube furnace was oxygen with a flow rate of 400 mL / min, a heat treatment temperature of 300-500 °C, and a holding time of 1-3 h to obtain NiO / TiO 2 powder.
[0022] Step 3: NiO / TiO 2 The powder was mixed with pine alcohol and coated on Al 2 O 3 The ceramic tube and the surface of the annular Au electrode are calcined at high temperature. After cooling in the furnace, the Ni-Cr heating wire is passed through the ceramic tube. Four Pt wire pins and two heating wire pins are welded on the hexagonal base to obtain a high-performance NiO-based acetone gas sensor. The gas sensing performance of the gas sensor is evaluated. The specific method is as follows: Step 3.1: NiO / TiO 2 The powder and pinene alcohol are mixed into a slurry with a certain viscosity, NiO / TiO 2 The powder mass and pineol volume ratio is 0.03~0.06:12~17 mg / μL, and then the slurry is evenly coated on the Al 2 O 3 Ceramic tube surface and ring-shaped Au electrode; Step 3.2: Then coat the NiO / TiO 2 Powdered Al 2 O 3 The ceramic tube was placed in a muffle furnace and calcined at 350-380 ℃ for 2-2.5 h to fully volatilize the pine alcohol. After cooling in the furnace, the Ni-Cr heating wire was passed through the ceramic tube, and four Pt wire pins and two heating wire pins were welded on the hexagonal base to obtain a high-performance NiO-based acetone gas sensor. Step 3.3: Place a high-performance NiO-based acetone gas sensor into a gas reaction chamber for gas sensing. Use a DC regulated power supply as a heating source to control the working temperature of the gas sensor by adjusting the output power. Use an electrochemical workstation to measure and record the resistance value. Inject a detection gas of a certain concentration and humidity into the reaction chamber to detect the resistance change and evaluate the NiO / TiO 2 Gas sensing performance.
[0023] The gas to be detected is acetone, methanol, xylene or isopropanol, the gas concentration is 3~300 ppm, the reaction temperature is 240~400 ℃, and the reaction humidity is 10~85%.
[0024] The high-performance NiO-based acetone gas-sensitive sensor element is prepared by the high-performance NiO-based acetone gas-sensitive sensor element preparation method.
[0025] By growing NiO on the surface of a small amount of ultra-thin n-type semiconductor in a monodispersed manner and using a freeze-drying method to reduce the agglomeration of the gas-sensitive material, NiO has a higher specific surface area and more pn junctions, ensuring that the NiO-based gas sensor has a higher response value on the basis of the P-type response. 3 C2 T x Introduced into NiO composite material system. 3 C 2 T x As a new type of two-dimensional (2D) layered structured MXene material, it has attracted extensive attention due to its high specific surface area and rich surface active functional groups. 3 C 2 T x It can not only serve as a growth site for metal oxides, but also be easily oxidized into n-type TiO in an oxygen atmosphere. 2 , and continue its flake-like morphology. By combining NiO nanosheets with larger specific surface area with Ti 3 C 2 T x Derived lamellar TiO 2 Composite can construct p-NiO / n-TiO 2 Heterostructure. Using NiO nanosheets and TiO 2 The geometric effect of the 2D / 2D combination of nanosheets and the freeze-drying method can not only avoid the accumulation of NiO nanosheets and increase the effective gas adsorption / desorption area of NiO nanosheets, but also make p-NiO and n-TiO 2 More heterogeneous interfaces are formed. This will help reduce the hole concentration on the NiO surface, ultimately increasing the response value of the NiO gas sensor and improving its selectivity.
[0026] Example 1 The preparation method of high-performance NiO-based acetone gas-sensitive sensor element comprises the following specific steps: Step 1: Few-layer Ti 3 C 2 T x Preparation of suspension Step 1.1, add 1.56 g of lithium fluoride into 20 mL of hydrochloric acid, the concentration of which is 12 mol / L, to obtain a hydrofluoric acid etching solution; Step 1.2, 1.0 g of titanium carbide aluminum powder was added to the hydrofluoric acid etching solution three times, and stirred at 45 ° C for 24 h to obtain a mixture, and the mixture was repeatedly washed with 3 mol / L dilute hydrochloric acid and deionized water until the pH of the upper clear liquid reached about 6 to obtain a multilayer Ti 3 C 2 T x Solution; Step 1.3: Multilayer Ti 3 C 2 T x The solution was dispersed in deionized water and ultrasonically treated at 30 °C for 3 h. The dark green supernatant was collected by centrifugation to obtain a few-layer Ti3 C 2 T x Suspension, few layers of Ti 3 C 2 T x The morphology of the nanosheets is Figure 1 shown.
[0027] Step 2: NiO / TiO 2 Synthesis of composite materials Step 2.1, 0.524g nickel nitrate hexahydrate, 1g hexadecyltrimethylammonium bromide and 0.037g few-layer Ti 3 C 2 T x The suspension is sequentially dispersed in a mixed solution of methanol and deionized water to obtain a hydrothermal solution, wherein the mass ratio of nickel nitrate hexahydrate, methanol and deionized water is 1:100:20.
[0028] Step 2.2, the hydrothermal solution was transferred to a 80 mL polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at a temperature of 180 °C for 24 h. After the hydrothermal reaction was completed, the hydrothermal product was washed 3 times with anhydrous ethanol and then 3 times with deionized water to obtain Ni(OH) 2 / Ti 3 C 2 T x Aqueous solution; Step 2.3: Ni(OH) 2 / Ti 3 C 2 T x The aqueous solution was freeze-dried at -20°C for 24 hours to obtain fluffy Ni(OH) 2 / Ti 3 C 2 T x Precursor; Step 2.4: Ni(OH) 2 / Ti 3 C 2 T x The precursor was placed in a tube furnace for a one-step heat treatment. The atmosphere in the tube furnace was oxygen with a flow rate of 400 mL / min and a heating rate of 5°C / min. The temperature was kept at 400°C for 2 h to obtain NiO / TiO 2 Powder, NiO / TiO 2 The SEM images are as follows Figure 2 shown.
[0029] Step 3: P-type NiO / TiO 2 Fabrication and performance testing of acetone gas sensor Step 3.1, 0.03 mg NiO / TiO 2 The powder was mixed with 12 μL of pinene alcohol to form a slurry with a certain viscosity, and then the slurry was evenly coated on the Al 2 O 3 Ceramic tube surface and ring-shaped Au electrode; Step 3.2: Then coat the NiO / TiO 2 Powdered Al 2 O 3 The ceramic tube was placed in a muffle furnace and calcined at 350°C for 2 hours to fully volatilize the pine alcohol. After cooling in the furnace, the Ni-Cr heating wire was passed through the ceramic tube, and four Pt wire pins and two heating wire pins were welded on the hexagonal base to obtain a high-performance NiO-based acetone gas sensor. Step 3.3, place the high-performance NiO-based acetone gas sensor into the gas reaction chamber for gas sensing, use a DC regulated power supply as a heating source, adjust the output power to 0.8W to make the working temperature of the gas sensor 340℃, and use an electrochemical workstation to measure and record the resistance value. Inject 3~300ppm acetone gas into the reaction chamber and calculate the NiO / TiO 2 The response value of the gas sensor, such as Figure 3 As shown in the figure, the NiO / TiO prepared by this method 2 The response value of the gas sensor to 100 ppm acetone is about 12 times higher than that of the NiO gas sensor, showing excellent gas sensing performance.
[0030] Example 2 The preparation method of high-performance NiO-based acetone gas-sensitive sensor element comprises the following specific steps: Step 1: Few-layer Ti 3 C 2 T x Preparation of suspension Step 1.1, add 1.56 g of lithium fluoride into 20 mL of hydrochloric acid, the concentration of which is 5 mol / L, to obtain a hydrofluoric acid etching solution; Step 1.2, take 1.0g titanium carbide aluminum powder and add it to the hydrofluoric acid etching solution for 5 times, stir it at 50℃ for 20h to obtain a mixture, and wash the mixture repeatedly with 3 mol / L dilute hydrochloric acid and deionized water until the pH of the supernatant reaches about 6 to obtain a multilayer Ti 3 C 2 T x Solution; Step 1.3: Multilayer Ti 3 C 2 T xThe solution was dispersed in deionized water and ultrasonically treated at 30 °C for 1 h. The dark green supernatant was collected by centrifugation to obtain a few-layer Ti 3 C 2 T x Suspension.
[0031] Step 2: NiO / TiO 2 Synthesis of composite materials Step 2.1, 0.524g nickel nitrate hexahydrate, 1g hexadecyltrimethylammonium bromide and 0.037g few-layer Ti 3 C 2 T x The suspension (7 wt %) was sequentially dispersed in a mixed solution of methanol and deionized water to obtain a hydrothermal solution, wherein the mass ratio of nickel nitrate hexahydrate, methanol and deionized water was 1:100:20.
[0032] Step 2.2, the hydrothermal solution was transferred to a 80 mL polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction, the hydrothermal temperature was 200 ° C, the hydrothermal time was 12 h, after the hydrothermal reaction was completed, the hydrothermal product was washed twice with anhydrous ethanol, and then washed four times with deionized water to obtain Ni(OH) 2 / Ti 3 C 2 T x Aqueous solution; Step 2.3: Ni(OH) 2 / Ti 3 C 2 T x The aqueous solution was freeze-dried at -50 °C for 12 h to obtain fluffy Ni(OH) 2 / Ti 3 C 2 T x Precursor; Step 2.4: Ni(OH) 2 / Ti 3 C 2 T x The precursor was placed in a tube furnace for a one-step heat treatment. The atmosphere in the tube furnace was oxygen with a flow rate of 400 mL / min and a heating rate of 5°C / min. The temperature was kept at 500°C for 1 h to obtain NiO / TiO 2 powder.
[0033] Step 3: P-type NiO / TiO 2 Fabrication and performance testing of acetone gas sensor Step 3.1, 0.06 mg NiO / TiO 2The powder was mixed with 17 μL of pinene alcohol to form a slurry with a certain viscosity, and then the slurry was evenly coated on the Al 2 O 3 Ceramic tube surface and ring-shaped Au electrode; Step 3.2: Then coat the NiO / TiO 2 Powdered Al 2 O 3 The ceramic tube was placed in a muffle furnace and calcined at 380°C for 2.5 hours to fully volatilize the pine alcohol. After cooling in the furnace, the Ni-Cr heating wire was passed through the ceramic tube, and four Pt wire pins and two heating wire pins were welded on the hexagonal base to obtain a high-performance NiO-based acetone gas sensor. Step 3.3, place the high-performance NiO-based acetone gas sensor in the gas reaction chamber for gas sensing. Use a DC regulated power supply as the heating source, adjust the output power to 0.8W, and make the working temperature of the gas sensor 340℃. Use an electrochemical workstation to measure and record the resistance value. Inject 7 gases (methanol, xylene, acetone, isopropanol, ethanol, formaldehyde, and ammonia) with a concentration of 100ppm into the reaction chamber, and use different saturated salt solutions to prepare the environment with a relative humidity of 10%~84%. Calculate the NiO / TiO 2 The response value of the gas sensor, such as Figure 4 , 5 As shown in the figure, the NiO / TiO prepared by this method 2 The gas sensor has the highest response value to acetone, and the response value can reach 188% at a high humidity of 84%, showing excellent selectivity and moisture resistance. Under the condition of 340℃, 100ppm acetone gas was released for 10 consecutive times to a 7 wt% sample. Figure 6 As shown in the figure, it can be seen that the NiO / TiO2 gas sensor prepared by this method exhibits excellent cycle stability for acetone.
[0034] Example 3 The preparation method of high-performance NiO-based acetone gas-sensitive sensor element comprises the following specific steps: Step 1: Few-layer Ti 3 C 2 T x Preparation of suspension Step 1.1, add 1.56 g of lithium fluoride into 20 mL of hydrochloric acid, the concentration of which is 10 mol / L, to obtain a hydrofluoric acid etching solution; Step 1.2, 1.0 g of titanium carbide aluminum powder was added to the hydrofluoric acid etching solution three times, and stirred at 48 ° C for 22 h to obtain a mixture, and the mixture was repeatedly washed with 3 mol / L dilute hydrochloric acid and deionized water until the pH of the upper clear liquid reached about 6 to obtain a multilayer Ti3 C 2 T x Solution; Step 1.3: Multilayer Ti 3 C 2 T x The solution was dispersed in deionized water and ultrasonically treated at a temperature of 50°C for 6 h. The dark green supernatant was collected by centrifugation to obtain a 0.02 g / mL few-layer Ti3C2Tx suspension.
[0035] Step 2: NiO / TiO 2 Synthesis of composite materials Step 2.1, 0.524g nickel nitrate hexahydrate, 1g hexadecyltrimethylammonium bromide and 0.016g few-layer Ti 3 C 2 T x The suspension is sequentially dispersed in a mixed solution of methanol and deionized water to obtain a hydrothermal solution, wherein the mass ratio of nickel nitrate hexahydrate, methanol and deionized water is 1:100:20.
[0036] Step 2.2, the hydrothermal solution was transferred to a 80 mL polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction, the hydrothermal temperature was 100 ° C, the hydrothermal time was 36 h, after the hydrothermal reaction was completed, the hydrothermal product was washed 4 times with anhydrous ethanol, and then washed 2 times with deionized water to obtain Ni(OH) 2 / Ti 3 C 2 T x Aqueous solution; Step 2.3: Ni(OH) 2 / Ti 3 C 2 T x The aqueous solution was freeze-dried at a temperature of -30°C and a freezing time of 36 h to obtain fluffy Ni(OH) 2 / Ti 3 C 2 T x Precursor; Step 2.4: Ni(OH) 2 / Ti 3 C 2 T x The precursor was placed in a tube furnace for a one-step heat treatment. The atmosphere in the tube furnace was oxygen with a flow rate of 400 mL / min and a heating rate of 5°C / min. The temperature was kept at 300°C for 3 h to obtain NiO / TiO 2 powder.
[0037] Step 3: P-type NiO / TiO 2Fabrication and performance testing of acetone gas sensor Step 3.1, 0.05 mg NiO / TiO 2 The powder was mixed with 17 μL of pinene alcohol to form a slurry with a certain viscosity, and then the slurry was evenly coated on the Al 2 O 3 Ceramic tube surface and ring-shaped Au electrode; Step 3.2: Then coat the NiO / TiO 2 Powdered Al 2 O 3 The ceramic tube was placed in a muffle furnace and calcined at 350°C for 2 hours to fully volatilize the pine alcohol. After cooling in the furnace, the Ni-Cr heating wire was passed through the ceramic tube, and four Pt wire pins and two heating wire pins were welded on the hexagonal base to obtain a high-performance NiO-based acetone gas sensor. Step 3.3, place the high-performance NiO-based acetone gas sensor into the gas reaction chamber for gas sensing, use a DC regulated power supply as a heating source, adjust the output power to 0.8W so that the operating temperature of the gas sensor is 400°C, and use an electrochemical workstation to measure and record the resistance value.
[0038] Example 4 The preparation method of high-performance NiO-based acetone gas-sensitive sensor element comprises the following specific steps: Step 1: Few-layer Ti 3 C 2 T x Preparation of suspension Step 1.1, add 1.56 g of lithium fluoride into 20 mL of hydrochloric acid, the concentration of which is 8 mol / L, to obtain a hydrofluoric acid etching solution; Step 1.2, 1.0 g of titanium carbide aluminum powder was added to a hydrofluoric acid etching solution in four times, and stirred at 50 ° C for 24 h to obtain a mixture, and the mixture was repeatedly washed with 3 mol / L dilute hydrochloric acid and deionized water until the pH of the upper clear liquid reached about 6 to obtain a multilayer Ti 3 C 2 T x Solution; Step 1.3: Multilayer Ti 3 C 2 T x The solution was dispersed in deionized water and ultrasonically treated at 25 °C for 6 h. The dark green supernatant was collected by centrifugation to obtain 0.02 g / mL TiO2. 3 C 2 T x Suspension.
[0039] Step 2: NiO / TiO 2 Synthesis of composite materials Step 2.1: 0.5 g nickel nitrate hexahydrate, 1 g hexadecyltrimethylammonium bromide and 0.037 g Ti 3 C 2 T x The suspension is sequentially dispersed in a mixed solution of methanol and deionized water to obtain a hydrothermal solution, wherein the mass ratio of nickel nitrate hexahydrate, methanol and deionized water is 1:100:20.
[0040] Step 2.2, the hydrothermal solution was transferred to a 80 mL polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction, the hydrothermal temperature was 150 ° C, the hydrothermal time was 30 h, after the hydrothermal reaction was completed, the hydrothermal product was washed 3 times with anhydrous ethanol, and then washed 3 times with deionized water to obtain Ni(OH) 2 / Ti 3 C 2 T x Aqueous solution; Step 2.3: Ni(OH) 2 / Ti 3 C 2 T x The aqueous solution was freeze-dried at -20°C for 36 hours to obtain fluffy Ni(OH) 2 / Ti 3 C 2 T x Precursor; Step 2.4: Ni(OH) 2 / Ti 3 C 2 T x The precursor was placed in a tube furnace for a one-step heat treatment. The atmosphere in the tube furnace was oxygen with a flow rate of 400 mL / min and a heating rate of 5°C / min. The temperature was kept at 400°C for 2 h to obtain NiO / TiO 2 powder.
[0041] Step 3: P-type NiO / TiO 2 Fabrication and performance testing of acetone gas sensor Step 3.1, 0.05 mg NiO / TiO 2 The powder was mixed with 15 μL of pinene alcohol to form a slurry with a certain viscosity, and then the slurry was evenly coated on the Al 2 O 3 Ceramic tube surface and ring-shaped Au electrode; Step 3.2: Then coat the NiO / TiO 2 Powdered Al 2 O 3The ceramic tube was placed in a muffle furnace and calcined at 350°C for 2 hours to fully volatilize the pine alcohol. After cooling in the furnace, the Ni-Cr heating wire was passed through the ceramic tube, and four Pt wire pins and two heating wire pins were welded on the hexagonal base to obtain a high-performance NiO-based acetone gas sensor. Step 3.3, place the high-performance NiO-based acetone gas sensor into the gas reaction chamber for gas sensing, use a DC regulated power supply as a heating source, adjust the output power so that the gas sensor works at the optimal temperature, and use an electrochemical workstation to measure and record the resistance value.
[0042] Example 5 The preparation method of high-performance NiO-based acetone gas-sensitive sensor element comprises the following specific steps: Step 1: Few-layer Ti 3 C 2 T x Preparation of suspension Step 1.1, add 1.56 g of lithium fluoride into 20 mL of hydrochloric acid, the concentration of which is 12 mol / L, to obtain a hydrofluoric acid etching solution; Step 1.2, 1.0 g of titanium carbide aluminum powder was added to the hydrofluoric acid etching solution three times, and stirred at 45 ° C for 24 h to obtain a mixture, and the mixture was repeatedly washed with 3 mol / L dilute hydrochloric acid and deionized water until the pH of the upper clear liquid reached about 6 to obtain a multilayer Ti 3 C 2 T x Solution; Step 1.3: Multilayer Ti 3 C 2 T x The solution was dispersed in deionized water and ultrasonically treated at 60 °C for 5 h. The dark green supernatant was collected by centrifugation to obtain 0.02 g / mL TiO2. 3 C 2 T x Suspension.
[0043] Step 2: NiO / TiO 2 Synthesis of composite materials Step 2.1, 0.55g nickel nitrate hexahydrate, 1g hexadecyltrimethylammonium bromide and 0.037g few-layer Ti 3 C 2 T x The suspension is sequentially dispersed in a mixed solution of methanol and deionized water to obtain a hydrothermal solution, wherein the mass ratio of nickel nitrate hexahydrate, methanol and deionized water is 1:100:20.
[0044] Step 2.2, the hydrothermal solution was transferred to a 80 mL polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at a temperature of 170 °C for 20 h. After the hydrothermal reaction was completed, the hydrothermal product was washed 4 times with anhydrous ethanol and then 4 times with deionized water to obtain Ni(OH) 2 / Ti 3 C 2 T x Aqueous solution; Step 2.3: Ni(OH) 2 / Ti 3 C 2 T x The aqueous solution was freeze-dried at -40 °C for 30 h to obtain fluffy Ni(OH) 2 / Ti 3 C 2 T x Precursor; Step 2.4: Ni(OH) 2 / Ti 3 C 2 T x The precursor was placed in a tube furnace for a one-step heat treatment. The atmosphere in the tube furnace was oxygen with a flow rate of 400 mL / min and a heating rate of 5°C / min. The temperature was kept at 500°C for 2 h to obtain NiO / TiO 2 powder.
[0045] Step 3: P-type NiO / TiO 2 Fabrication and performance testing of acetone gas sensor Step 3.1, 0.05 mg NiO / TiO 2 The powder was mixed with 15 μL of pinene alcohol to form a slurry with a certain viscosity, and then the slurry was evenly coated on the Al 2 O 3 Ceramic tube surface and ring-shaped Au electrode; Step 3.2: Then coat the NiO / TiO 2 Powdered Al 2 O 3 The ceramic tube was placed in a muffle furnace and calcined at 350°C for 2 hours to fully volatilize the pine alcohol. After cooling in the furnace, the Ni-Cr heating wire was passed through the ceramic tube, and four Pt wire pins and two heating wire pins were welded on the hexagonal base to obtain a high-performance NiO-based acetone gas sensor. Step 3.3, place the high-performance NiO-based acetone gas sensor into the gas reaction chamber for gas sensing, use a DC regulated power supply as a heating source, adjust the output power so that the gas sensor works at the optimal temperature, and use an electrochemical workstation to measure and record the resistance value.
[0046] Example 6 The preparation method of high-performance NiO-based acetone gas-sensitive sensor element comprises the following specific steps: Step 1: Few-layer Ti 3 C 2 T x Preparation of suspension Step 1.1, add 1.56 g of lithium fluoride into 20 mL of hydrochloric acid, the concentration of which is 8 mol / L, to obtain a hydrofluoric acid etching solution; Step 1.2, 1.0 g of titanium carbide aluminum powder was added to a hydrofluoric acid etching solution in four times, and stirred at 50 ° C for 24 h to obtain a mixture, and the mixture was repeatedly washed with dilute hydrochloric acid and deionized water until the pH of the upper clear liquid reached about 6 to obtain a multilayer Ti 3 C 2 T x Solution; Step 1.3: Multilayer Ti 3 C 2 T x The solution was dispersed in deionized water and ultrasonically treated at 60 °C for 4 h. The dark green supernatant was collected by centrifugation to obtain a few-layer Ti 3 C 2 T x Suspension.
[0047] Step 2: NiO / TiO 2 Synthesis of composite materials Step 2.1, 0.524g nickel nitrate hexahydrate, 1g hexadecyltrimethylammonium bromide and 0.035g few-layer Ti 3 C 2 T x The suspension is sequentially dispersed in a mixed solution of methanol and deionized water to obtain a hydrothermal solution, wherein the mass ratio of nickel nitrate hexahydrate, methanol and deionized water is 1:100:20.
[0048] Step 2.2, the hydrothermal solution was transferred to a 80 mL polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at a temperature of 190 °C for 26 h. After the hydrothermal reaction was completed, the hydrothermal product was washed 4 times with anhydrous ethanol and then 4 times with deionized water to obtain Ni(OH) 2 / Ti 3 C 2 T x Aqueous solution; Step 2.3: Ni(OH) 2 / Ti 3 C 2 T xThe aqueous solution was freeze-dried at -50 °C for 36 h to obtain fluffy Ni(OH) 2 / Ti 3 C 2 T x Precursor; Step 2.4: Ni(OH) 2 / Ti 3 C 2 T x The precursor was placed in a tube furnace for a one-step heat treatment. The atmosphere in the tube furnace was oxygen with a flow rate of 400 mL / min and a heating rate of 5°C / min. The temperature was kept at 350°C for 2 h to obtain NiO / TiO 2 powder.
[0049] Step 3: P-type NiO / TiO 2 Fabrication and performance testing of acetone gas sensor Step 3.1, 0.04 mg NiO / TiO 2 The powder was mixed with 15 μL of pinene alcohol to form a slurry with a certain viscosity, and then the slurry was evenly coated on the Al 2 O 3 Ceramic tube surface and ring-shaped Au electrode; Step 3.2: Then coat the NiO / TiO 2 Powdered Al 2 O 3 The ceramic tube was placed in a muffle furnace and calcined at 370°C for 2.5 hours to fully volatilize the pine alcohol. After cooling in the furnace, the Ni-Cr heating wire was passed through the ceramic tube, and four Pt wire pins and two heating wire pins were welded on the hexagonal base to obtain a high-performance NiO-based acetone gas sensor. Step 3.3, place the high-performance NiO-based acetone gas sensor into the gas reaction chamber for gas sensing, use a DC regulated power supply as a heating source, adjust the output power so that the gas sensor works at the optimal temperature, and use an electrochemical workstation to measure and record the resistance value.
Claims
1. A method for preparing a high-performance NiO-based acetone gas-sensitive sensor element, characterized in that: The specific steps are as follows: Step 1: Mix lithium fluoride and hydrochloric acid, add titanium aluminum carbide and stir evenly, and wash with dilute hydrochloric acid and deionized water to obtain multilayer Ti3C2T x solution, and then multilayer Ti3C2T x The solution was dispersed in deionized water and ultrasonically treated to obtain a few-layer Ti3C2T x Suspension; Step 2: Nickel nitrate hexahydrate, hexadecyltrimethylammonium bromide and few-layer Ti3C2T x The suspension is dispersed in a mixed solution of methanol and deionized water in turn, and then subjected to a hydrothermal reaction, and finally washed, freeze-dried and heat-treated to obtain NiO / TiO2 powder; Step 3: Mix the NiO / TiO2 powder with pinene alcohol and coat the mixture on the surface of the Al2O3 ceramic tube and the annular Au electrode, perform high-temperature calcination, and pass the Ni-Cr heating wire through the ceramic tube after cooling in the furnace. Weld 4 Pt wire pins and 2 heating wire pins on the hexagonal base to obtain a high-performance NiO-based acetone gas sensor, and evaluate the gas sensing performance of the gas sensor.
2. The method for preparing the high-performance NiO-based acetone gas sensitive sensor element according to claim 1, characterized in that: The specific method of step 1 is: Step 1.1, adding lithium fluoride to hydrochloric acid and mixing evenly to obtain a hydrofluoric acid etching solution; Step 1.2: Take titanium carbide aluminum powder and add it to a hydrofluoric acid etching solution in 3 to 5 times, stir it at 45°C to 50°C for 20 to 24 hours to obtain a mixture, and wash the mixture with 3 mol / L dilute hydrochloric acid and deionized water respectively until the pH of the supernatant reaches 5.9 to 6.1 to obtain a multilayer Ti3C2T x Solution; Step 1.3: Multilayer Ti3C2T x The solution was dispersed in deionized water and ultrasonically treated, centrifuged and the dark green supernatant was collected to obtain the few-layer Ti3C2T x Suspension.
3. The method for preparing a high-performance NiO-based acetone gas-sensitive sensor element according to claim 2, characterized in that: In the step 1.1, the molar ratio of lithium fluoride to hydrochloric acid is 1:4, and the concentration of the hydrochloric acid is 5-12M; in the step 1.2, the mass ratio of lithium fluoride to titanium aluminum carbide powder is 1.55-1.58:
1.
4. The method for preparing a high-performance NiO-based acetone gas-sensitive sensor element according to claim 2, characterized in that: In step 1.3, the multilayer Ti3C2T x The solution was ultrasonically treated at a temperature of 25-70 °C for 1-6 h. x The concentration of the suspension is 0.01~0.1 g / mL.
5. The method for preparing the high-performance NiO-based acetone gas sensitive sensor element according to claim 1, characterized in that: The specific method of step 2 is: Step 2.1: Add a certain amount of nickel nitrate hexahydrate, hexadecyltrimethylammonium bromide and few-layer Ti3C2T x The suspension is sequentially dispersed in a mixed solution of methanol and deionized water to obtain a hydrothermal solution; Step 2.2, the hydrothermal solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene for hydrothermal reaction, the hydrothermal temperature is 100-200 ° C, the hydrothermal time is 12-36 hours, after the hydrothermal reaction is completed, the hydrothermal product is washed 2-4 times with anhydrous ethanol, and then washed 2-4 times with deionized water to obtain Ni(OH)2 / Ti3C2T x Aqueous solution; Step 2.3: Ni(OH)2 / Ti3C2T x The aqueous solution was freeze-dried at a temperature of -20 to -50 °C and a freezing time of 12 to 36 h to obtain fluffy Ni(OH)2 / Ti3C2T x Precursor; Step 2.4: Ni(OH)2 / Ti3C2T x The precursor is placed in a tube furnace for a one-step heat treatment to obtain NiO / TiO2 powder.
6. The method for preparing a high-performance NiO-based acetone gas-sensitive sensor element according to claim 5, characterized in that: In the step 2.1, the mass ratio of nickel nitrate hexahydrate to hexadecyltrimethylammonium bromide is 0.5-0.55:1, and the few-layer Ti3C2T x The mass percentage of nickel nitrate hexahydrate is 1-15wt%; The mass ratio of the nickel nitrate hexahydrate, methanol and deionized water is 1:100:
20.
7. The method for preparing a high-performance NiO-based acetone gas-sensitive sensor element according to claim 5, characterized in that: In step 2.4, the atmosphere in the tubular furnace is oxygen, the flow rate is 400 mL / min, the heat treatment temperature is 300-500°C, and the holding time is 1-3 h.
8. The method for preparing a high-performance NiO-based acetone gas sensitive sensor element according to claim 1, characterized in that: The specific method of step 3 is: Step 3.1, mixing the NiO / TiO2 powder and pinene alcohol into a slurry with a certain viscosity, wherein the mass ratio of the NiO / TiO2 powder to the pinene alcohol is 0.03-0.06:12-17 mg / μL, and then evenly coating the slurry on the surface of the Al2O3 ceramic tube and the annular Au electrode; Step 3.2, then placing the Al2O3 ceramic tube coated with NiO / TiO2 powder in a muffle furnace, calcining at 350-380°C for 2-2.5 h to fully volatilize the pine alcohol, and after cooling in the furnace, passing the Ni-Cr heating wire through the ceramic tube, and welding 4 Pt wire pins and 2 heating wire pins on the hexagonal base to obtain a high-performance NiO-based acetone gas sensor; Step 3.3, placing the high-performance NiO-based acetone gas sensor into a gas reaction chamber for gas sensing, using a DC regulated power supply as a heating source, controlling the operating temperature of the gas sensor by adjusting the output power, using an electrochemical workstation to measure and record the resistance value, injecting a detection gas of a certain concentration and humidity into the reaction chamber, detecting the resistance change, and evaluating the gas sensing performance of NiO / TiO2.
9. The method for preparing a high-performance NiO-based acetone gas sensitive sensor element according to claim 8, characterized in that: The gas to be detected introduced in step 3.3 is acetone, methanol, xylene or isopropanol, the gas concentration is 3-300 ppm, the reaction temperature is 240-400°C, and the reaction humidity is 10-85%.
10. A high performance NiO-based acetone gas-sensitive sensor element prepared by the method for preparing a high performance NiO-based acetone gas-sensitive sensor element according to any one of claims 1 to 9.